2003
DOI: 10.1089/154041903322716697
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Low-Carbohydrate, Unlimited Calorie Diet on the Treatment of Childhood Obesity: A Prospective Controlled Study

Abstract: A high protein, low carbohydrate, unlimited calorie diet was superior to a restricted calorie protocol for weight loss in obese school age children; moreover, compliance was better.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
18
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 19 publications
4
18
0
1
Order By: Relevance
“…There are more favorable effects on plasma lipid profile with the low‐carbohydrate diet 13 . The studies on the use of low‐carbohydrate diets on pediatric age groups have increased recently and the results are encouraging 14,15 . Although there are some reports on adults that diet therapy reverses the effects of obesity on ventricular functions, 28,29 to the best of our knowledge, this is the only study examining the effects of diet therapy and weight reduction on left ventricular function in childhood obesity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are more favorable effects on plasma lipid profile with the low‐carbohydrate diet 13 . The studies on the use of low‐carbohydrate diets on pediatric age groups have increased recently and the results are encouraging 14,15 . Although there are some reports on adults that diet therapy reverses the effects of obesity on ventricular functions, 28,29 to the best of our knowledge, this is the only study examining the effects of diet therapy and weight reduction on left ventricular function in childhood obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Conventional therapy for obesity is a low‐lipid, low‐calorie diet. A low‐carbohydrate diet is shown to be a reasonable alternative to conventional diet for decreasing insulin resistance, reversing dyslipidemia and reducing weight in adults 12,13 and in children 14,15 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In a controlled but not randomized trial, Bailes et al showed an increased weight loss with a non‐energy‐restricted ketogenic diet compared with a low‐calorie diet (LCal) in children. In this trial, the LC group lost an average of 5.21 kg, while the LCal group gained an average of 2.36 kg (53). They did not report lipid data.…”
Section: Types Of Controlled Carbohydrate Approachesmentioning
confidence: 71%
“…In a pilot study, Bailes et al [42] studied 55 5-to 18-year-old obese children who chose either a lowcarbohydrate diet (max 30 g CHO/day) or a standard low-calorie diet (max. 30 E% fat, 15 to 20 E% protein, and 55 E% CHO; 80% of calculated energy need).…”
Section: Low-carbohydrate Diet Studies In Childrenmentioning
confidence: 99%